Forecasting euro area inflation using targeted predictors: is money coming back? - Matteo Falagiarda; Jo\~ao Sousa (European Central Bank (ECB), 2017)
This paper sheds new light on the information content of monetary and credit aggregates for future price developments in the euro area. Overall, we find strong variation in the information content of these variables over time. We show that monetary and credit aggregates are very often selected among the top predictors of inflation, with their predictive power relative to other predictors generally improving in the post-2012 period. An out-of-sample forecasting exercise indicates that, when monetary and credit aggregates are loaded directly in the forecasting equation, the additional gains over the benchmark model are generally high and significant across horizons and HICP components only in the most recent period. When the forecasts are computed using factor-augmented regressions based on the best predictors, we confirm the importance of monetary and credit variables in forecasting inflation, even if their information content is diluted in a much broader pool of variables.
Keywords: C53; E37; E41; E51; E58; 330; diffusion index; forecasting; inflation; money; targeted predictors